Assessment of the Socioeconomic Implications of the Higher Education Students Loans Board on Tanzanian Students - Antoniammal M; Renuka Devi (Management Science Research Journal, 2026)
This paper will discuss the role played by the Higher Education Students Loans Board (HESLB) in determining the socioeconomic status of the Tanzanian students with special focus on the effectiveness of the organization in providing fair accessibility to higher education and the overall economic mobility of the students. The collection of quantitative and qualitative data was done on a few selected universities using a mixed-methods approach, among loan beneficiaries, non-recipients, and higher education administrators. The research analyzes the impact of loan distribution policies, loan repayment and efficiency of loan disbursement on students with various socioeconomic backgrounds. The results show that although the HESLB has greatly expanded access to higher education for low-income students, differences in loan distribution and repayment capacity still exist. Financial issues caused by stringent repayment conditions, postponed pay outs, and restricted loan coverage have impeded the intended sustainability and inclusion goals. The study comes to the conclusion that the Board's role in promoting fair and sustainable higher education funding in Tanzania will grow if loan appraisal and recovery procedures are changed, especially by implementing income-contingent repayment plans and open allocation procedures.